T Cells Cause Acute Immunopathology and Are Required for Long-Term Survival in Mouse Adenovirus Type 1-Induced Encephalomyelitis - Moore, Martin L. (American Society for Microbiology, 2003)
Infection of adult C57BL/6 (B6) mice with mouse adenovirus type 1 (MAV-1) results in dose-dependent encephalomyelitis. Utilizing immunodeficient mice, we analyzed the roles of T cells, T-cell subsets, and T-cell-related functions in MAV-1-induced encephalomyelitis. T cells, major histocompatibility complex (MHC) class I, and perforin contributed to acute disease signs at 8 days postinfection (p.i.). Acute MAV-1-induced encephalomyelitis was absent in mice lacking T cells and in mice lacking perforin. Mice lacking α/β T cells had higher levels of infectious MAV-1 at 8 days, 21 days, and 12 weeks p.i., and these mice succumbed to MAV-1-induced encephalomyelitis at 9 to 16 weeks p.i. Thus, α/β T cells were required for clearance of MAV-1. MAV-1 was cleared in mice lacking perforin, MHC class I or II, CD4(+) T cells, or CD8(+) T cells. Our results are consistent with a model in which either CD8(+) or CD4(+) T cells are sufficient for clearance of MAV-1. Furthermore, perforin contributed to MAV-1 disease but not viral clearance. We have established two critical roles for T cells in MAV-1-induced encephalomyelitis. T cells caused acute immunopathology and were required for long-term host survival of MAV-1 infection.